Blade of the immortal volume 16 ebook Shortcut. - Samura, Hiroaki (Blade of the Immortal, 2018)
As Rin frets over her bodyguard Manji's disappearance, she is surprised by the arrival of two traveling warriors, the feisty, headstrong Döa Yoshino and her huge, brutish companion, Isaku Yasono-ökami. Rin quickly regrets her decision to let this strange couple stay with her, but her detective work takes priority when she returns to the stronghold of Habaki Kagamura to search for Manji. Meanwhile, Kagimura's medical examiners begin to test the seemingly immortal Manji, who is imprisoned, chained and a very unwilling toy in their merciless hands!